Detrito exótico altera a decomposição da matéria orgânica, mas não a biodiversidade de macroinvertebrados. - Contieri, Beatriz Bosquê (2018)
We hypothesized that an exotic species modifies the biodiversity of aquatic invertebrates and the decomposition process under the prediction that the greater the proportion of the exotic species, the lower the biodiversity of macroinvertebrates and consequently the slower the decomposition process. The study was conducted in first order streams of the Atlantic Forest with a native species (Cariniana estrellensis) and an exotic species (Psidium guajava). We defined treatments with different proportions of each species (0 to 100%), which were removed from the streams in different periods of submersion (15, 30, 45, 60 and 90 days). The macroinvertebrates were identified at the family level and the leaf processing rates (k) and the remaining leaf ratio were calculated. It was observed a reduction of the processing mediated by the exotic species, while the invertebrate biodiversity was variable between the treatments and throughout the processing. The nutritional properties of the litter determined the colonization by macroinvertebrates and led the decomposition process. The use of litter as an indirect and structural food resource was attributed to high biodiversity indexes in the exotic and low relation with the rate decomposition. It is suggested that the effect of the exotic species be investigated over time regarding changes in the chemical properties of the litter and consequent effect on the aquatic biota.